Platelet-derived β2m regulates age related monocyte/macrophage functions - Hilt, Zachary T. (Aging (Albany NY), 2019)
Platelets have central roles in both immune responses and development. Stimulated platelets express leukocyte adhesion molecules and release numerous immune modulatory factors that recruit and activate leukocytes, both at the sites of activation and distantly. Monocytes are innate immune cells with dynamic immune modulatory functions that change during the aging process, a phenomenon termed “inflammaging”. We have previously shown that platelets are a major source of plasma beta-2 microglobulin (β2M) and that β2M induced a monocyte pro-inflammatory phenotype. Plasma β2M increases with age and is a pro-aging factor. We hypothesized that platelet derived β2M regulates monocyte phenotypes in the context of aging. Using wild-type (WT) and platelet specific β2M knockout mice (Plt-β2M(-/-)) mice, we found that plasma β2M increased with age and correlated with increased circulating Ly6C(Hi) monocytes. However, aged Plt-β2M(-/-) mice had significantly fewer Ly6C(Hi) monocytes compared to WT mice. Quantitative real-time PCR of circulating monocytes showed that WT mouse monocytes were more “pro-inflammatory” with age, while Plt-β2M(-/-) derived monocytes adopted a “pro-reparative” phenotype. Older Plt-β2M(-/-) mice had a significant decline in heart function compared to age matched WT mice, as well as increased cardiac fibrosis and pro-fibrotic markers. These data suggest that platelet-derived β2M regulates age associated monocyte polarization, and a loss of platelet derived β2M shifted monocytes and macrophages to a pro-reparative phenotype and increased pro-fibrotic cardiac responses. Platelet regulation of monocyte phenotypes via β2M may maintain a balance between inflammatory and reparative signals that affects age related physiologic outcomes.